Epstein-Barr virus (EBV) and systemic lupus erythematosus (SLE) association in serological studies - Czyż, Witold; Chuncia-Ileczko, Marta; Wójcikiewicz, Michalina; Arczewski, Filip; Dziedzic, Karol; Kulbacka, Julia; Wojszczyk, Maciej; Zys, Damian; Pasek, Piotr; Ryniecka, Julia (Quality in Sport, 2025)
Over the past 50 years, a substantial body of research revealed an association between Epstein-Barr virus (EBV), and various aspects of EBV infection, with multiple autoimmune diseases. Growing evidence points to EBV as a potential co-factor in systemic lupus erythematosus (SLE) and several mechanisms have been proposed to explain this relationship, however there is as yet no conclusive proof of causality. This literature review constitutes an introduction into the subject and attempts to outline the findings on the EBV-SLE connection, focusing mostly on the evidence provided by serological studies.